A biodegradable plastic particle and its preparation method and application
The problem of poor flexibility and strength is solved by adding specific modifiers and other additives to the PLA and PBAT blends, and higher plastic particle performance is achieved, making it suitable for applications requiring high strength and toughness.
Patent Information
- Application Number
- CN202411896240.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The flexibility and strength of the PLA and PBAT blends are difficult to meet certain application needs.
Specific modifiers are added to plastic particles with PLA and PBAT as matrix, such as polylactic acid-polyethylene glycol block copolymers, polycaprolactone-polyglycidyl methacrylate block copolymers with mass ratios of 1:19~19:1, as well as other toughening agents, lubricants and fillers to improve their flexibility and strength.
Significantly improves the flexibility and strength of plastic particles, making them more suitable for applications requiring high strength and toughness, such as degradable straws and cheese sticks.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of degradable plastics, and in particular to biodegradable plastic particles, a preparation method and application thereof. Background Art
[0002] With growing environmental awareness, biodegradable plastics are attracting increasing attention. Based on their raw material source, biodegradable plastics can be categorized as bio-based, petrochemical-based, and natural polymer biodegradable plastics. Bio-based biodegradable plastics include polylactic acid (PLA), polyhydroxyalkanoic acid (PHA), and poly-β-hydroxybutyric acid (PHB); petrochemical-based biodegradable plastics include polybutylene adipate-terephthalate (PBAT), polybutylene succinate (PBS), polycaprolactone (PCL), and polyvinyl alcohol (PVA); and natural polymer biodegradable plastics include starch, cellulose, and chitin. Among these biodegradable plastics, PLA and PBAT are the most widely used. PLA has good rigidity and mechanical properties, but is brittle and lacks ductility. PBAT has good toughness and film-forming properties, but suffers from insufficient rigidity and reduced strength. Blending PLA with PBAT can complement their properties.
[0003] However, direct blending of PLA and PBAT results in poor compatibility, resulting in relatively poor overall performance of the blend, such as flexibility and strength. Therefore, improving the flexibility and strength of biodegradable plastic particles based on PLA and PBAT blends is a current research focus. Summary of the Invention
[0004] The present invention provides biodegradable plastic particles, a preparation method and application thereof, which solve the problem of poor flexibility and strength of plastic particles in the related art.
[0005] The technical solutions of the present invention are as follows:
[0006] The present invention provides a biodegradable plastic particle comprising the following components in parts by weight:
[0007] PLA 50-80 parts, PBAT 20-50 parts, filler 5-20 parts, toughening agent 1-8 parts, lubricant 1-5 parts, modifier 5-10 parts;
[0008] The modifier includes a polylactic acid-polyethylene glycol block copolymer and a polycaprolactone-polyglycidyl methacrylate block copolymer in a mass ratio of 1:19 to 19:1.
[0009] As a further technical solution, the modifier includes a polylactic acid-polyethylene glycol block copolymer and a polycaprolactone-polyglycidyl methacrylate block copolymer in a mass ratio of 5:3-8.
[0010] In the present invention, a modifier comprising a polylactic acid-polyethylene glycol block copolymer and a polycaprolactone-polyglycidyl methacrylate block copolymer in a mass ratio of 5:3-8 is added to plastic particles based on PLA and PBAT, thereby further improving the flexibility and strength of the plastic particles.
[0011] As a further technical solution, the toughening agent includes one or two of polyvinyl alcohol and acetyl tributyl citrate; the lubricant includes one or more of stearic acid, lauric acid, and oleic acid.
[0012] As a further technical solution, the filler includes an organic filler and an inorganic filler.
[0013] As a further technical solution, the mass ratio of the organic filler to the inorganic filler is 1:1 to 1:3.
[0014] As a further technical solution, the organic filler includes one or more of starch, wood powder, bamboo powder, and fruit shell powder.
[0015] As a further technical solution, the inorganic filler includes one or more of talc, calcium carbonate, and silicon dioxide.
[0016] As a further technical solution, the particle size of the inorganic filler is 15-50 nm.
[0017] As a further technical solution, the inorganic filler is further modified with ethylene bisstearamide.
[0018] As a further technical solution, the modification method comprises the following steps: mixing the inorganic filler with an ethylene bisstearamide solution and drying;
[0019] The mass ratio of the inorganic filler to the ethylene bisstearamide solution is 1:2-3;
[0020] The mass ratio of ethylene bisstearamide to solvent in the ethylene bisstearamide solution is 1:8-12.
[0021] In the present invention, the inorganic filler is modified with ethylene bisstearamide and then added to the plastic particles, thereby further improving the strength of the plastic particles.
[0022] The present invention also provides a method for preparing the biodegradable plastic particles, comprising the following steps:
[0023] The components of the biodegradable plastic particles are mixed, extruded and granulated to obtain plastic particles.
[0024] The present invention also proposes the use of the biodegradable plastic particles or the plastic particles prepared by the preparation method in degradable plastic products.
[0025] In the present invention, the degradable plastic product may be, for example, a degradable straw, a cheese stick, or the like.
[0026] The drinking straw made of the biodegradable plastic particles of the present invention has the characteristics of light weight, high hardness and good toughness.
[0027] The working principle and beneficial effects of the present invention are:
[0028] In the present invention, the biodegradable plastic particles are based on PLA and PBAT, and polylactic acid-polyethylene glycol block copolymer and polycaprolactone-polyglycidyl methacrylate block copolymer are added in a mass ratio of 1:19 to 19:1 as modifiers, which significantly improves the flexibility and strength of the plastic particles. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0030] In the following examples and comparative examples, polylactic acid-polyethylene glycol block copolymer was purchased from Xi'an Qiyue Biotechnology Co., Ltd., item number Q-0013694;
[0031] Polycaprolactone-poly(glycidyl methacrylate) block copolymer was purchased from Xi'an Ruixi Biotechnology Co., Ltd., product number R-SG-972.
[0032] Example 1
[0033] Biodegradable plastic particles, comprising the following components in parts by weight:
[0034] PLA (weight average molecular weight 100,000) 80 parts, PBAT (model TH801T) 20 parts, filler 5 parts, acetyl tributyl citrate 1 part, stearic acid 1 part, modifier 5 parts;
[0035] The filler is an organic filler and an inorganic filler in a mass ratio of 1:2;
[0036] The organic filler is wood powder; the inorganic filler is talc powder (particle size 50nm) and calcium carbonate (particle size 15nm) in a mass ratio of 1:3;
[0037] The modifier is a polylactic acid-polyethylene glycol block copolymer and a polycaprolactone-polyglycidyl methacrylate block copolymer in a mass ratio of 1:19;
[0038] The method for preparing biodegradable plastic particles comprises the following steps:
[0039] The components of the biodegradable plastic particles are mixed and extruded into granules to obtain the plastic particles.
[0040] Example 2
[0041] Biodegradable plastic particles, comprising the following components in parts by weight:
[0042] 50 parts of PLA (weight average molecular weight 100,000), 50 parts of PBAT (model TH801T), 20 parts of filler, 8 parts of acetyl tributyl citrate, 2 parts of stearic acid, 3 parts of lauric acid, and 10 parts of modifier;
[0043] The filler is an organic filler and an inorganic filler in a mass ratio of 1:3;
[0044] The organic filler is wood powder; the inorganic filler is talc powder (particle size 30nm) and silicon dioxide (particle size 15nm) in a mass ratio of 1:3;
[0045] The modifier is a polylactic acid-polyethylene glycol block copolymer and a polycaprolactone-polyglycidyl methacrylate block copolymer in a mass ratio of 19:1;
[0046] The method for preparing biodegradable plastic particles comprises the following steps:
[0047] The components of the biodegradable plastic particles are mixed and extruded into granules to obtain the plastic particles.
[0048] Example 3
[0049] Biodegradable plastic particles, comprising the following components in parts by weight:
[0050] PLA (weight average molecular weight 100,000) 60 parts, PBAT (model TH801T) 40 parts, filler 12 parts, acetyl tributyl citrate 4 parts, stearic acid 2 parts, lauric acid 3 parts, modifier 8 parts;
[0051] The filler is an organic filler and an inorganic filler in a mass ratio of 1:1;
[0052] The organic filler is wood powder; the inorganic filler is talc powder (particle size 30nm) and calcium carbonate (particle size 15nm) in a mass ratio of 1:3;
[0053] The modifier is a polylactic acid-polyethylene glycol block copolymer and a polycaprolactone-polyglycidyl methacrylate block copolymer in a mass ratio of 5:2;
[0054] The method for preparing biodegradable plastic particles comprises the following steps:
[0055] The components of the biodegradable plastic particles are mixed and extruded into granules to obtain the plastic particles.
[0056] Example 4
[0057] The only difference between this embodiment and embodiment 3 is that the modifier is a polylactic acid-polyethylene glycol block copolymer and a polycaprolactone-polyglycidyl methacrylate block copolymer in a mass ratio of 5:3.
[0058] Example 5
[0059] The only difference between this embodiment and embodiment 3 is that the modifier is a polylactic acid-polyethylene glycol block copolymer and a polycaprolactone-polyglycidyl methacrylate block copolymer in a mass ratio of 5:8.
[0060] Example 6
[0061] The only difference between this embodiment and embodiment 3 is that the modifier is a polylactic acid-polyethylene glycol block copolymer and a polycaprolactone-polyglycidyl methacrylate block copolymer in a mass ratio of 5:9.
[0062] Example 7
[0063] The only difference between this embodiment and embodiment 4 is that the inorganic filler is replaced by a stearamide-modified inorganic filler. The preparation method of the stearamide-modified inorganic filler includes the following steps:
[0064] The inorganic filler and the stearamide solution were mixed at a mass ratio of 1:2, and dried to obtain a stearamide-modified inorganic filler;
[0065] The mass ratio of stearamide to chloroform in the stearamide solution is 1:8.
[0066] Example 8
[0067] The only difference between this embodiment and embodiment 4 is that the inorganic filler is replaced with an ethylene bisstearamide modified inorganic filler. The preparation method of the ethylene bisstearamide modified inorganic filler comprises the following steps:
[0068] The inorganic filler and the ethylene bisstearamide solution were mixed at a mass ratio of 1:2, and dried to obtain an ethylene bisstearamide modified inorganic filler;
[0069] The mass ratio of ethylene bisstearamide to chloroform in the ethylene bisstearamide solution is 1:8.
[0070] Example 9
[0071] The only difference between this embodiment and embodiment 4 is that the inorganic filler is replaced with an ethylene bisstearamide modified inorganic filler. The preparation method of the ethylene bisstearamide modified inorganic filler comprises the following steps:
[0072] The inorganic filler and the ethylene bisstearamide solution were mixed at a mass ratio of 1:3, and dried to obtain an ethylene bisstearamide modified inorganic filler;
[0073] The mass ratio of ethylene bisstearamide to chloroform in the ethylene bisstearamide solution is 1:12.
[0074] Comparative Example 1
[0075] The only difference between this comparative example and Example 3 is that the polylactic acid-polyethylene glycol block copolymer is replaced by a polycaprolactone-polyglycidyl methacrylate block copolymer.
[0076] Comparative Example 2
[0077] The only difference between this comparative example and Example 3 is that the polycaprolactone-polyglycidyl methacrylate block copolymer is replaced by a polylactic acid-polyethylene glycol block copolymer.
[0078] 1. The following performance tests were performed on the plastic pellets extruded into sheets obtained in Examples 1 to 9 and Comparative Examples 1 to 2:
[0079] Tensile strength: After making a 1A dumbbell-shaped specimen in accordance with the standard GB / T 1040.2-2022 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics", the tensile strength test was carried out in accordance with the standard GB / T 1040.1-2018 "Determination of tensile properties of plastics Part 1: General principles" at a test speed of 1 mm / min;
[0080] Impact strength: The notched cantilever beam impact strength test was conducted in accordance with the standard GB / T 1843-2008 “Plastics — Determination of cantilever beam impact strength”. The specimen size (length × width × thickness) was 80 mm × 10 mm × 4 mm, and the notch type was A.
[0081] The test results are shown in Table 1 below:
[0082] Table 1 Performance test results
[0083]
[0084] Compared with Comparative Examples 1 to 2, the tensile strength and notched Izod impact strength of the plastic particles prepared in Examples 1 to 9 are higher, indicating that the plastic particles are based on PLA and PBAT, and the addition of polylactic acid-polyethylene glycol block copolymer and polycaprolactone-polyglycidyl methacrylate block copolymer in a mass ratio of 1:19 to 19:1 as modifiers significantly improves the flexibility and strength of the plastic particles.
[0085] Compared with Examples 3 and 6, the tensile strength and notched Izod impact strength of the plastic particles prepared in Examples 4 to 5 are higher, indicating that the addition of modifiers such as polylactic acid-polyethylene glycol block copolymer and polycaprolactone-polyglycidyl methacrylate block copolymer in a mass ratio of 5:3 to 8 to the plastic particles based on PLA and PBAT further improves the flexibility and strength of the plastic particles.
[0086] Compared with Example 7, the tensile strength of the plastic particles prepared in Examples 8-9 is higher, indicating that the inorganic filler modified with ethylene bisstearamide and then added to the plastic particles further improves the strength of the plastic particles.
[0087] 2. The plastic particles prepared in Example 3 were used as test materials for biodegradability testing:
[0088] The biodegradability percentage was calculated according to the standard GB / T 19277.1-2011 "Determination of the ultimate aerobic biodegradability of materials under controlled composting conditions by measuring the released carbon dioxide - Part 1: General method". The reference material was microcrystalline cellulose, and the compost was 3 months old. The test results are shown in Table 2 below. The relative biodegradability percentage of the test material = the biodegradability percentage of the test material / the biodegradability percentage of the reference material.
[0089] Table 2 Biodegradability test results
[0090]
[0091] 3. Application Examples
[0092] 3.1 Straw
[0093] The plastic particles obtained in Example 3 were made into straws and used as test materials for biodegradability testing:
[0094] The biodegradability percentage was calculated according to the standard GB / T 19277.1-2011 "Determination of the ultimate aerobic biodegradability of materials under controlled composting conditions by measuring the released carbon dioxide - Part 1: General method". The reference material was microcrystalline cellulose, and the compost was 3 months old. The test results are shown in Table 3 below.
[0095] Table 3 Biodegradability test results
[0096]
[0097] 3.2 Cheese Sticks
[0098] The plastic particles prepared in Example 3 were made into cheese sticks, and the performance of the prepared cheese sticks was tested.
[0099] Fluorescence test: Wash the cheese stick sample with distilled water, dry it, and then place it under ultraviolet light with a wavelength of 254nm and 365nm for fluorescence test. The cheese stick is qualified if the cumulative area of the fluorescent spots does not exceed 5% of the area of a single package.
[0100] The final fluorescence test result is: qualified.
[0101] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A biodegradable plastic particle, characterized in that: The composition comprises the following components in parts by weight: PLA 50-80 parts, PBAT 20-50 parts, filler 5-20 parts, toughening agent 1-8 parts, lubricant 1-5 parts, modifier 5-10 parts; The modifier includes a polylactic acid-polyethylene glycol block copolymer and a polycaprolactone-polyglycidyl methacrylate block copolymer in a mass ratio of 1:19 to 19:
1.
2. The biodegradable plastic particles according to claim 1, characterized in that: The modifier includes a polylactic acid-polyethylene glycol block copolymer and a polycaprolactone-polyglycidyl methacrylate block copolymer in a mass ratio of 5:3-8.
3. The biodegradable plastic particles according to claim 1, characterized in that: The toughening agent includes one or two of polyvinyl alcohol and acetyl tributyl citrate; the lubricant includes one or more of stearic acid, lauric acid and oleic acid.
4. The biodegradable plastic particles according to claim 1, characterized in that: The filler includes organic filler and inorganic filler.
5. The biodegradable plastic particles according to claim 4, characterized in that: The organic filler includes one or more of starch, wood powder, bamboo powder and fruit shell powder.
6. The biodegradable plastic particles according to claim 4, characterized in that: The inorganic filler includes one or more of talc, calcium carbonate and silicon dioxide.
7. The biodegradable plastic particles according to claim 6, characterized in that: The inorganic filler is also modified by ethylene bisstearamide.
8. The biodegradable plastic particles according to claim 7, characterized in that: The modification method comprises the following steps: mixing the inorganic filler with ethylene bisstearamide solution and drying; The mass ratio of the inorganic filler to the ethylene bisstearamide solution is 1:2-3; The mass ratio of ethylene bisstearamide to solvent in the ethylene bisstearamide solution is 1:8-12.
9. The method for preparing biodegradable plastic particles according to any one of claims 1 to 8, characterized in that: The following steps are involved: The components of the biodegradable plastic particles are mixed, extruded and granulated to obtain plastic particles.
10. Use of the biodegradable plastic particles according to any one of claims 1 to 8 or the plastic particles prepared by the preparation method according to claim 9 in degradable plastic products.
Citation Information
Patent Citations
Full-biodegradable blending material
CN113354934A
Polylactic acid composite material and preparation method thereof
CN115449178A